1976
DOI: 10.1080/09553007614551251
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEvaluation of Some Latent Radioprotective Compounds

Abstract: In tissue culture, protection against X-irradiation by a number of cysteamine derivatives was studied and the results were compared with data obtained in mice. Compounds with a covered SH group, like WR 638, cysteamine phosphate, WR 2721, and AE 48527, showed practically no protection when dissolved in tissue-culture medium, but developed a protective activity when dissolved in rat blood. Thiol measurements demonstrated that in rat blood the compounds were partly hydrolysed to thiols. C511 was also hydrolysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These results further suggest that it is the sulfhydryl group or the presence of a disulfide bond that seems necessary for compounds to inhibit ST activity. Until now, research with thiols and disulfides as therapeutic agents has centered on their radioprotective properties (3,4,34,39) and their efficacy in the treatment of acetaminophen overdoses (2,11,27,35,36) and nephropathic cystinosis (38,41).…”
Section: Resultsmentioning
confidence: 99%
“…These results further suggest that it is the sulfhydryl group or the presence of a disulfide bond that seems necessary for compounds to inhibit ST activity. Until now, research with thiols and disulfides as therapeutic agents has centered on their radioprotective properties (3,4,34,39) and their efficacy in the treatment of acetaminophen overdoses (2,11,27,35,36) and nephropathic cystinosis (38,41).…”
Section: Resultsmentioning
confidence: 99%
“…Like 2mercaptoethylamine, they are all actual or potential aminothiols. AET undergoes rearrangement in neutral aqueous solutions to form mercaptoethylguanidine (43); with WR2721, the phosphate group shielding the thiol can be removed by hydrolysis to yield the active compound WR1065 (34,51,54). Unlike WR1065, WR2721 was ineffective in reversing STa activation of guanylate cyclase (Table 2), and we concluded that its ineffectiveness was a result of its relatively slow rate of dephosphorylation by BBMV under the conditions of the guanylate cyclase assay.…”
Section: Discussionmentioning
confidence: 92%
“…We therefore decided not to exclude AET and BAL from in vivo testing. WR1065, WR2721, and AET were developed for chemical protection against ionizing radiation (43,54). Like 2mercaptoethylamine, they are all actual or potential aminothiols.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical radioprotectors exert their protective effects through scavenging of free radicals[3]. A variety of compounds that act as chemical radioprotectors have been described including agents such as amifostine and other thiols,[4,5] nitroxides, [6-8] polyphenols,[9] tocols,[10] ethyl pyruvate,[11] superoxide dismutase mimetics,[12,13], melatonin and its homologues,[14] and other free radical scavengers. (reviewed in [15]).…”
Section: Introductionmentioning
confidence: 99%